Can Somatotrophs and Thyrotrophs Recover from the Effects of Diazepam after its Withdrawal? An Ultrastructure Study - Soad S. Ali; Nasra N. Ayoub; Manal M. Shehata; Sanaa M. Abdelalateif (Journal of King Abdulaziz University: Medical Sciences, 2023)
This study aimed to detect the effects of long term administration of diazepam on the ultrastructure of somatotrophs and thyrotrophs of the anterior pituitary, and the possibility of recovering from its effects after withdrawal. Forty male adult rats used in this study were divided into a control and experimental groups. The latter was divided into two subgroups; first received diazepam intraperitoneally at a daily dose of 0.18 mg/200 gm body weight for 21 days. The second was left for one month after stopping the diazepam, which was given for same period. The pars distalis of the pituitary glands were dissected and processed for light and electron microscopic study. Most of the somatotrophs showed signs of degeneration following administration of diazepam for 21 days. Thyrotrophs showed variable degrees of effect, but to a lesser extent compared to somatotrophs. After withdrawal of diazepam, most of the somatotrophs showed irreversible changes, apart from few cells that appeared intact. Some thyrotrophs recovered from the effects of diazepam while others could not. In conclusion, withdrawal of diazepam did not allow the affected somatotrophs and thyrotrophs to recover from its harmful effect. Therefore, diazepam should be given cautiously, especially when treating children.